Exploring Local Potential as a Source for Banyumasan Children's Songs - Emah Winangsit; Sunarto Sunarto; Udi Utomo; Syahrul Syah Sinaga; Fajry Sub'haan Syah Sinaga (International Conference on Science, Education, and Technology, 2022)
Abstract. This article discusses the local potential in Banyumas which can be used as the main idea in making Banyumasan children's songs. Local potential consists of physical and non-physical, including tourism, ngapak dialect, cablaka, and babad Banyumasan. This potential can be expressed in the form of children's songs that have educational messages through art. Musicological analysis with an art phenomenological approach is used to see the process of selecting local potential that can be used as inspiration in making children's songs. This study aims to analyze the growing local potential in the Banyumas area which can be a source of inspiration in making Banyumasan children's songs. This research is a type of qualitative research using several musicological and phenomenological studies. The results showed that the local potential in Banyumas can be seen from traditional children's games, cablaka characters, natural charm, and tourism in Banyumas. Based on the analysis carried out by researchers, they found a simple formula about the use of local potential as a source of inspiration in making children's songs, including: the tone chosen must be simple according to the character of the nursery rhyme, there are educational messages based on locality values, the use of language that is interesting and easy to understand by children.